Tipologi Pemahaman Hadis (Studi Pemikiran Hadis Mahmud Saltut) - Ach Baiquni (IAIN Bengkulu, 2019)
Most Muslim societies especially in Indonesia understand that all traditions contain innocence but in reality scholars try to reclassify that in understanding the traditions, people who will understand the traditions must know and sort out and choose whether the traditions that contain shariah or not, Mahmud Syaltut is present to offering this theory, so that the Islamic Community is not complacent that everything contained in the hadith contains Shariah, even though it is not because in living everyday life the Prophet Muhammad works as the head of the State, the Messenger of God, the husband, the father of his child and the leader of the war. Now this is what makes the reason someone who wants to understand the hadith must know the text and context of the hadith. The purpose of this study is to elaborate on the thought of the Hadith Mahmud Syaltut about how to understand the hadith, while the research method is literature by examining the book by Mahmud Syaltut